1993
DOI: 10.1128/mcb.13.9.5829
|View full text |Cite
|
Sign up to set email alerts
|

SPK1 is an essential S-phase-specific gene of Saccharomyces cerevisiae that encodes a nuclear serine/threonine/tyrosine kinase.

Abstract: SPKI was originally discovered in an immunoscreen for tyrosine-protein kinases in Saccharomyces cerevisiae. MATERIALS AND METHODS Plasmids. pSK9-15 and pSK15-9 are Bluescript plasmids (Stratagene Cloning Systems) carrying a 3.6-kbp EcoRI fragment including SPK1 coding and upstream sequences (52); pNB187 was obtained from Peter Novick (Yale University School of Medicine); clnl::URA3 and pH2AB1 were obtained from Fred Cross (Rockefeller University); pRS303, pRS305, pRS315, and pRS316 (51) were obtained from Aaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 53 publications
6
78
0
1
Order By: Relevance
“…Similar results were obtained for Hhp2. On the basis of this behavior (Kuret and Schulman, (Zheng et al, 1993). Hhpl was examined in these experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were obtained for Hhp2. On the basis of this behavior (Kuret and Schulman, (Zheng et al, 1993). Hhpl was examined in these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The Mcklp gene product is important for yeast kinetochore function in mitosis and for early meiotic gene expression (Neigeborn and Mitchell, 1991;Shero and Hieter, 1991). The Spklp protein kinase is an essential S-phase-specific gene product that is a nuclear Ser/Thr/Tyr kinase (Zheng et al, 1993). It is suggested that Spklp plays an important role in regulating DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The family of proteins containing FHA domains, which includes proteins of diverse functional roles, is growing rapidly. Examples of the FHA family include: Dun1 and Rad53 (or Spk1), which are involved in DNA damage repair and the S phase checkpoint in Saccharomyces cerevisiae (Allen et al, 1994;Navas et al, 1995;Sun et al, 1998;Zheng et al, 1993); Cds1, the Schizosaccharomyces pombe homolog of Rad53 (Murakami & Okayama, 1995); Mek1, which is related to meitotic recombination of yeast (Leem & Ogawa, 1992); KAPP, kinase-associated protein phosphatase from Arobidopsis thaliana, which binds to the receptorlike protein kinase RLK5 (Stone et al, 1994); and Ki-67, a human nuclear protein related to cell proliferation (Schluter et al, 1993). The two most recent members are HuCds1 (or Chk2) in humans (Brown et al, 1999;Matsuoka et al, 1998), and Dmnk in Drosophila melanogaster (Oishi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The RAD53 gene also contains two similar cis-acting-elements in its promoter that up-regulate its expression at late G1-/S-phase [17]. Cell-cycle regulation of Rad53 may be important for S-phase specific inhibition of Sml1 to release RNR activity during a normal S-phase.…”
Section: Discussionmentioning
confidence: 99%